2007
DOI: 10.1143/jpsj.76.093702
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Neutron Scattering from Phase IV of Ce0.7La0.3B6: A Confirmation of the Octupole Order

Abstract: We have performed a single crystal neutron scattering experiment on Ce0.7La0.3B6 to microscopically investigate the order parameter of phase IV. Below the phase transition temperature 1.5 K of phase IV, weak but distinct superlattice reflections at the scattering vector κ = () (h, l = odd number) have been observed for the first time by neutron scattering. The intensity of the superlattice reflections is stronger for high scattering vectors, which is quite different from the usual magnetic form factor of magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 23 publications
2
50
0
Order By: Relevance
“…Lanthanum doping of CeB 6 suppresses both AFM and AFQ phases and induces a new multipolar-ordered phase IV beyond a quantum critical point (QCP) at x ≈ 0.3, presumably of octupolar character [57][58][59]. Non-Fermi-liquid behavior has been observed in the vicinity of the QCP [60], and a recent specific-heat investigation of substituted Ce 1−x La x B 6 emphasizes the importance of multipolar fluctuations that are directly linked to the effective mass of charge carriers [61].…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanum doping of CeB 6 suppresses both AFM and AFQ phases and induces a new multipolar-ordered phase IV beyond a quantum critical point (QCP) at x ≈ 0.3, presumably of octupolar character [57][58][59]. Non-Fermi-liquid behavior has been observed in the vicinity of the QCP [60], and a recent specific-heat investigation of substituted Ce 1−x La x B 6 emphasizes the importance of multipolar fluctuations that are directly linked to the effective mass of charge carriers [61].…”
Section: Introductionmentioning
confidence: 99%
“…2. It is remarkable that the magnon is more intense around the Γ (110) point than at the equivalent Γ (001) or Γ (000) positions [49], suggesting an anomalous nonmonotonic behavior of the dynamic form factor that is characteristic of multipolar moments (for conventional dipolar moments, it would decrease monotonically with |Q|) [50][51][52]. A magnetic field of 2.5 T [ Fig.…”
mentioning
confidence: 99%
“…First, we have clarified the selection rules for the octupolar scattering on the basis of a symmetry analysis of the cross section. Then, we have discussed the magnetic form factor for phase IV of Ce 1−x La x B 6 , and have shown that a recent observation by Kuwahara et al 13) can be interpreted as the first example of the octupolar scattering. The possibility of observing the spectra for ordered octupoles in NpO 2 and field-induced octupoles in AFQ phases have been pointed out.…”
Section: Discussionmentioning
confidence: 95%
“…13) They reported that distinct magnetic Bragg peaks have been observed in the short wave-length region, although the existence of the peak at κ = (1/2, 1/2, 1/2) is not clear. The form factor at κ = (5/2, 5/2, 5/2) is estimated to be of about 0.1µ B per one Ce ion.…”
Section: )mentioning
confidence: 99%